Profilin Isoforms Modulate Astrocytic Morphology and the Motility of Astrocytic Processes - Schweinhuber, Stefanie K. (PLoS One, 2015)
The morphology of astrocytic processes determines their close structural association with synapses referred to as the ‘tripartite synapse’. Concerted morphological plasticity processes at tripartite synapses are supposed to shape neuronal communication. Morphological changes in astrocytes as well as the motility of astrocytic processes require remodeling of the actin cytoskeleton. Among the regulators of fast timescale actin-based motility, the actin binding protein profilin 1 has recently been shown to control the activity-dependent outgrowth of astrocytic processes. Here, we demonstrate that cultured murine astrocytes in addition to the ubiquitous profilin 1 also express the neuronal isoform profilin 2a. To analyze the cellular function of both profilins in astrocytes, we took advantage of a shRNA mediated isoform-specific downregulation. Interestingly, consistent with earlier results in neurons, we found redundant as well as isoform-specific functions of both profilins in modulating cellular physiology. The knockdown of either profilin 1 or profilin 2a led to a significant decrease in cell spreading of astrocytes. In contrast, solely the knockdown of profilin 2a resulted in a significantly reduced morphological complexity of astrocytes in both dissociated and slice culture astrocytes. Moreover, both isoforms proved to be crucial for forskolin-induced astrocytic stellation. Furthermore, forskolin treatment resulted in isoform-specific changes in the phosphorylation level of profilin 1 and profilin 2a, leading to a PKA-dependent phosphorylation of profilin 2a. In addition, transwell assays revealed an involvement of both isoforms in the motility of astrocytic processes, while FRAP analysis displayed an isoform-specific role of profilin 1 in the regulation of actin dynamics in peripheral astrocytic processes. Taken together, we suggest profilin isoforms to be important modulators of astrocytic morphology and motility with overlapping as well as isoform-specific functions.